Effects of a lower limb rehabilitation robot with various training modes in patients with stroke: A randomized controlled trial - Junekyung Lee; Chun, Min Ho; Seo, Yu Jin; Anna Lee; Choi, Junho; Son, Choong hyun (Lippincott Williams & Wilkins Ltd., 2022)
Background: The effect of robot-assisted gait training has been demonstrated to improve gait recovery in patients with stroke. The aim of this study was to determine effects of robot-assisted gait training with various training modes in patients post stroke. Methods: Forty-seven patients post stroke were randomly assigned to one of 4 groups: Healbot T with pelvic off mode (pelvic off group; n = 11); Healbot T with pelvic control mode (pelvic on group; n = 12); Healbot T with constraint-induced movement therapy (CIMT) mode (CIMT group; n = 10); and conventional physiotherapy (control group; n = 10). All patients received a 30-minute session 10 times for 4 weeks. The primary outcomes were the 10-meter walk test (10MWT) and Berg Balance Scale (BBS). The secondary outcomes were functional ambulation category, timed up and go (TUG), and motricity index of the lower extremities (MI-Lower). Results: The pelvic off group showed significant improvements in BBS, TUG, and MI-Lower (P < .05). The pelvic on and CIMT groups showed significant improvement in 10MWT, BBS, TUG, and MI-Lower (P < .05). Compared with control group, the pelvic on group showed greater improvement in the TUG and BBS scores; the CIMT group showed greater improvement in 10MWT and MI-Lower (P < .05). Conclusion: This study suggested that Healbot T-assisted gait training benefited patients with stroke. The Healbot T with pelvic motion and CIMT modes were more helpful in improving balance and walking ability and lower limb strength, respectively, compared with conventional physiotherapy.